2011
DOI: 10.1525/auk.2011.10191
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Coconut Forest as Habitat for the Critically Endangered Tuamotu Kingfisher (Todiramphus Gambieri Gertrudae)

Abstract: The effects of anthropogenic habitat modification are evident on tropical Pacific islands where forests have been extensively converted to plantations of Coconut Palm {Cocos nucífera). We evaluated resource selection in the critically endangered Tuamotu Kingfisher {Todiramphus gambieri gertrudae), which is confined to a single population on the low-elevation island of Niau Atoll in French Polynesia. Our analyses indicate that resources associated with foraging underlie space use and habitat selection of Tuamot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…This endemic bird is confined to Niau and preferentially nests and forages within coconut groves located on the east side of the island, especially in semi-open and exploited groves ( Gouni et al 2006;Coulombe et al 2011;Thibault and Cibois 2017) (Figure 1). Between 1970 and 1990, the Niau kingfisher was reported as common (Seitre and Seitre 1992), with a population estimated at 400-600 individuals (Holyoak and Thibault 1984).…”
Section: The Niau Kingfisher T Gertrudaementioning
confidence: 99%
See 1 more Smart Citation
“…This endemic bird is confined to Niau and preferentially nests and forages within coconut groves located on the east side of the island, especially in semi-open and exploited groves ( Gouni et al 2006;Coulombe et al 2011;Thibault and Cibois 2017) (Figure 1). Between 1970 and 1990, the Niau kingfisher was reported as common (Seitre and Seitre 1992), with a population estimated at 400-600 individuals (Holyoak and Thibault 1984).…”
Section: The Niau Kingfisher T Gertrudaementioning
confidence: 99%
“…Recently, a demographic study (Kesler et al 2012) suggested that Niau kingfisher population dynamics could be limited by strong predation by cats and rats at critical demographic stages. Competition for food resources with introduced predators has also been suspected of impacting bird survival (Gouni and Sanford 2003;Coulombe et al 2011). However, insufficient data is available from which to construct a robust conservation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Synanthropic species cohabit with humans and benefit from anthropogenic landscapes. Examples of highly endangered synanthropic species are exceptionally scarce, with only two species heretofore recognized among birds—Sociable Lapwings ( Vanellus gregarious ; Kamp 2009) and Tuamotu Kingfishers ( Todiramphus gambieri gertrudae ; Coulombe et al 2011). Although saving synanthropic species seems intuitively straightforward, they can present unique challenges for conservation management because of potentially rapid cultural and evolutionary changes associated with landscape modification (Johnston 2001, Boardman 2006), reduced food availability (Tallamy 2004), other anthropogenic threats that counter the benefits of synanthropy (e.g., pesticide use, vehicle and window collisions, introduced predators), and partial continued dependence on natural habitats.…”
mentioning
confidence: 99%
“…Not all avian species will decline with human disturbance, and some may even benefit from resource subsidies and increases in open and edge habitats, including those within anthropogenic areas (Werner, Hejl & Brush, 2007; Kamp et al, 2009; Coulombe, Kesler & Gouni, 2011). The Bahama Oriole uses anthropogenic areas during the breeding season, where it selects nest sites in the tallest available palm trees (Price, Lee & Hayes, 2011).…”
Section: Discussionmentioning
confidence: 99%